2016
DOI: 10.1016/j.jsha.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness in metabolic syndrome

Abstract: Transthoracic echocardiographic determination of AVP is a simple practical method and correlates well with FMD in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…22 determine the arterial stiffness of many diseases such as HT, coronary artery disease, DM, and metabolic syndrome. 6,7,24,25 In our study, we investigated the relationship between AVP and TOD, and the predictive value on LVH and proteinuria. To the best of our knowledge, there is no study investigating the predictive value of the novel echocardiographic method APV on target organ damages LVH and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…22 determine the arterial stiffness of many diseases such as HT, coronary artery disease, DM, and metabolic syndrome. 6,7,24,25 In our study, we investigated the relationship between AVP and TOD, and the predictive value on LVH and proteinuria. To the best of our knowledge, there is no study investigating the predictive value of the novel echocardiographic method APV on target organ damages LVH and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The level of CRP has been associated with indices of arterial function in several populations ( 7 , 17 , 21 , 80 , 97 100 ). However, data regarding a possible direct etiological role of CRP in arterial dysfunction and atherosclerosis are contradictory, and there are also studies reporting no significant relationship between PWV and hsCRP ( 17 , 101 ).…”
Section: Crp High-sensitivity C-reactive Protein (Hscrp) and Arterimentioning
confidence: 99%
“…A significant correlation was reported between aortic flow propagation velocity (AVP), which is a parameter of reduced arterial stiffness, assessed by transthoracic echocardiography, and high CRP levels, which is indicating a link between aortic stiffness and inflammation ( 7 ). Several other cross-sectional studies demonstrated the link between metabolic syndrome, arterial stiffness, and inflammation ( 97 ).…”
Section: Crp High-sensitivity C-reactive Protein (Hscrp) and Arterimentioning
confidence: 99%
See 1 more Smart Citation
“…Вместе с тем, органопротекция остается важным аспектом при лечении артериальной гипертензии (АГ). В последнее время все большую значимость приобретает необходимость коррекции центрального АД, улучшения эластичности сосудов и влияния на так называемые "новые" факторы риска (С-реактивный белок (СРБ), гомоцистеин, лептин и адипонектин) [2][3][4][5]. Выявлены существенные различия между классами антигипертензивных препаратов и их отдельными представителями по влиянию на показатели эластичности сосудов различного калибра [6][7][8][9][10][11][12][13].…”
unclassified